Given equation is,
"f(x,y,z,p,q) = x(y^2+z^2\u00d7q^2)- zy^2p= xy^2+xz^2q^2- zy^2p"
Since, Transformation is, "T = \\frac{z^2}{2}"
Now,
"z = \\sqrt{2T}"
"p =\\frac{\\partial z}{\\partial x} = \\sqrt{2}\\frac{1}{2} T^{-1\/2}\\frac{\\partial T}{\\partial x} =\\frac{1}{\\sqrt{2T}} \\frac{\\partial T}{\\partial x} =\\frac{1}{\\sqrt{2T}} P"
"q=\\frac{\\partial z}{\\partial y} = \\sqrt{2}\\frac{1}{2} T^{-1\/2}\\frac{\\partial T}{\\partial y} =\\frac{1}{\\sqrt{2T}} \\frac{\\partial T}{\\partial y} =\\frac{1}{\\sqrt{2T}} Q"
Putting value of z, p and q in the given equation,
"xy^2+x(2T)(\\frac{1}{\\sqrt{2T}} Q)^2 -\\sqrt{2T} y^2 (\\frac{1}{\\sqrt{2T}} P)=0"
"xy^2+x(2T)(\\frac{1}{{2T}} Q^2) - y^2 ( P)=0"
"xy^2+xQ^2 - y^2 P=0"
"y^2(x-P) = -xQ^2"
"\\frac{y^2}{Q^2} = \\frac{x}{(P-x)}"
It can written as,
"g(Q,y) = f(P,x)"
which is the required result.
Comments
Leave a comment